2010
DOI: 10.1097/bot.0b013e3181ccba4b
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral Transfibular Approach to Tibial Plateau Fractures: Technique, Results, and Rationale

Abstract: We describe a posterolateral transfibular neck approach to the proximal tibia. This approach was developed as an alternative to the anterolateral approach to the tibial plateau for the treatment of two fracture subtypes: depressed and split depressed fractures in which the comminution and depression are located in the posterior half of the lateral tibial condyle. These fractures have proved particularly difficult to reduce and adequately internally fix through an anterior or anterolateral approach. The approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
79
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 10 publications
0
79
0
5
Order By: Relevance
“…Given the high incidence of 68.5% in tibial plateau fractures involving the posterior column and plenty of important anatomical structures locating in the posterolateral site of the knee, how to manage the posterolateral column remains a big challenge in clinical practice. The PRLA was designed, unlike early ones [18][19][20][21][22][23][24], not only for the management of posterior (both posteromedial and posterolateral) tibial plateau fractures but also, while combined with the anterolateral approach, all the three columns of tibial plateau could be exposed as a whole. For the posterolateral fragments management, the advantages and disadvantages of the PRLA had been discussed in early studies [5,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high incidence of 68.5% in tibial plateau fractures involving the posterior column and plenty of important anatomical structures locating in the posterolateral site of the knee, how to manage the posterolateral column remains a big challenge in clinical practice. The PRLA was designed, unlike early ones [18][19][20][21][22][23][24], not only for the management of posterior (both posteromedial and posterolateral) tibial plateau fractures but also, while combined with the anterolateral approach, all the three columns of tibial plateau could be exposed as a whole. For the posterolateral fragments management, the advantages and disadvantages of the PRLA had been discussed in early studies [5,7,25].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with plain radiographs, computed tomography (CT) scans can provide detailed information on intra-articular fractures. With the widespread use of CT, it has been found that in some cases, the fracture line may appear on the coronal plane and the split-depression fracture may be restricted in the posterolateral region, which is different from ordinary Schatzker type II fractures, as the visualisation of the fracture site was obstructed by the fibular head [8][9][10]. Inadequate vision or assessment of the fracture may lead to failure of primary fixation, and furthermore, secondary articular depression, valgus deformity and deterioration in the long-term [11].…”
Section: Introductionmentioning
confidence: 99%
“…An anterior or anterolateral approach has commonly been used. However, if the fracture line does not extend to the anterior tibial cortex, then osteotomy of the anterior tibial cortex might be required [11]. An anterior or anterolateral approach also cannot provide good visualisation of the posterior plateau because of the soft tissue structures of the posterolateral corner.…”
Section: Discussionmentioning
confidence: 96%